Narlim's Fingerprints: Aboriginal Histories and Rock Art. Issue 3 (3rd July 2021) - May, Sally K.; Rademaker, Laura; Goldhahn, Joakim; Taçon, Paul S. C.; Narndal Gumurdul, Julie
ABSTRACT: This article takes an interdisciplinary approach to understanding Aboriginal rock art artists, drawing together insights from the disciplines of archaeology and biography, as well as from Indigenous knowledge-holders, in order to explore the life and work of a relatively unknown rock painter from western Arnhem Land in Australia: Narlim (born c. 1909). His rock art at Warlkarr (Hawk Dreaming) in Kakadu National Park stands as subtle but powerful testament to his life, his family and unbroken connections to Country. Narlim's art reveals the ways he creatively engaged with new knowledges and skills introduced by the newcomers to his Country, even as he asserted the enduring traditions and ongoing sovereignty of his people. By reading rock art as a historical source alongside other biographical material, in partnership with Traditional Owners of today, we offer a fresh and holistic approach to better understanding rock art.